2021
DOI: 10.1002/psc.3334
|View full text |Cite
|
Sign up to set email alerts
|

Capacity for increased surface area in the hydrophobic core of β‐sheet peptide bilayer nanoribbons

Abstract: Amphipathic peptides with amino acids arranged in alternating patterns of hydrophobic and hydrophilic residues efficiently self‐assemble into β‐sheet bilayer nanoribbons. Hydrophobic side chain functionality is effectively buried in the interior of the putative bilayer of these nanoribbons. This study investigates consequences on self‐assembly of increasing the surface area of aromatic side chain groups that reside in the hydrophobic core of nanoribbons derived from Ac‐(XKXE)2‐NH2 peptides (X = hydrophobic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…P6 roughly exhibits amphipathic features composed of alternating hydrophilic (T and K) and hydrophobic residues (G, L, I, and A). Considering that amphipathic peptides can fold into β-sheets and self-assemble into β-sheet bilayer nanoribbons via sidechain hydrophobic functionality, , and that P6 can also form β-sheets as well as twisted nanoribbons, we reasoned that P6 probably employs its amphipathic features for self-assembly. P4 self-assembles into helical nanofibers and unique microrings in a pH-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…P6 roughly exhibits amphipathic features composed of alternating hydrophilic (T and K) and hydrophobic residues (G, L, I, and A). Considering that amphipathic peptides can fold into β-sheets and self-assemble into β-sheet bilayer nanoribbons via sidechain hydrophobic functionality, , and that P6 can also form β-sheets as well as twisted nanoribbons, we reasoned that P6 probably employs its amphipathic features for self-assembly. P4 self-assembles into helical nanofibers and unique microrings in a pH-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…This lipophilicity change is compatible with the AMPs being covalently linked to the surface by the CuAAC reaction. There were small differences between the peptides themselves with the same hydrophobic amino acids, but the biphenylalanine peptides ( 2a – d ) showed an overall higher contact angle than the tryptophan peptides ( 1a – d ) due to biphenylalanine being more hydrophobic than tryptophan [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In aqueous media, two sheets may self-assemble to form a β-sheet bilayer in which hydrophobic residues are buried inside, while the hydrophilic faces are exposed to the solvent. It has been demonstrated that this type of self-assembly can accommodate large aromatic side-chains in the inner shielded region and that increasing the area of the aromatic surface leads to stronger π-π interactions [ 37 ]. Thus, we expected to obtain self-assembled nanostructures with an aromatic core in which strong π-π interactions are established between BTBT chromophores.…”
Section: Resultsmentioning
confidence: 99%